KEEFEKTIFAN MODEL PEMBELAJARAN COMPLETE SENTENCE DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS III SDN 12 PATTENE - Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is how to apply the complete sentence learning model to improve the writing skills of third-grade students of Pattene Elementary School, Polsel District, Takalar Regency. The purpose of this study is to improve student learning outcomes in Indonesian language subjects through the application of the complete sentence learning model in the writing skills of third-grade students of Pattene Elementary School, Polsel District, Takalar Regency. This type of research is classroom action research consisting of two cycles, each cycle is carried out 3 times. The research procedure includes planning, implementation of actions, observation, and reflection. The subjects in this study were 12 third-grade elementary school students. The results of the student writing skills test in cycle I, whose score was 75 and above, only reached 54.00%, while in cycle II it increased to 86.36%. The average value of students' writing skills in cycle I was 5.95 and in cycle II it increased to 9.50. So it can be said that the average value of students' writing skills in cycle I to cycle II experienced an improvement of 3.56. Thus, the level of student learning completion from cycle I to cycle II increased by 32.36%. Based on the research results above, it can be concluded that the learning outcomes of Indonesian language in writing skills of grade III students of Pattene Elementary School, Polsel District, Takalar Regency through the complete sentence learning model have increased.